PENGARUH KARAKTERISTIK PERSONAL AUDITOR DAN EMOTIONAL SPIRITUAL QUOTIENT (ESQ) TERHADAP PENERIMAAN PERILAKU DISFUNGSIONAL AUDIT - Nadya Havel; Azwir Nasir; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to examine the effect of external locus of control, turnover intention, auditor self-rated performance and emotional spiritual quotient (ESQ) to the acceptance of dysfunctional audit behaviour. The samples of this research were public accountants in Pekanbaru, Padang and Batam. The results of this study showed that external locus of control had significant effect to the acceptance of dysfunctional audit behaviour, but turnover intention did not affect the acceptance of dysfunctional audit behaviour. While self-rated performance had significant effect to the acceptance of dysfunctional audit behaviour, ESQ also had significant effect to the acceptance of dysfunctional audit behaviour. Coefficient determination test results showed R2 value of 0.736 which means the contribution of the influence by independent variables on the dependent variable was 73.6%. While the remaining 26.4% was influenced by other variables that not included in this regression model.Keywords : Dysfunctional Audit Behaviour, Locus Of Control, Turnover Intention, Performance, ESQ